Effect of high-voltage spark discharges on reduction of the concentration of total bacterial count in wastewater. (February 2022) - Belov, Alexander; Vasilyev, Alexey; Dorokhov, Alexey; Izmailov, Andrey; Storchevoy, Vladimir
Abstract: The limited supply of fresh water on the planet stimulates the reuse of wastewater in various areas. It is proposed to use disinfected wastewater for irrigation in agriculture. The possibility of reducing the total bacterial count in wastewater by high-voltage spark discharges using a developed experimental setup has been investigated. The total bacterial count was measured by the rapid method using a luminometric mini-laboratory EnSURE Touch and a standard method for counting bacteria, capable of forming colony-forming units on nutrient agar. Wastewater from the Zhulebinsky storm collector with an initial concentration of 10 12 CFU ml −1 with a volume of 10 3 ml is disinfected up to the norm 6 log in 120 s with capacitance 0.1 μF and in 180 s with capacitance 0.05 μF. Wastewater from the Kuryanovsky storm channel with an initial concentration of 10 9 CFU ml −1 with a volume of 10 3 ml is disinfected up to the norm 6 log in 100 s with capacitance 0.1 μF and in 160 s with capacitance 0.05 μF. To reduce the concentration of total bacterial count by 1 log, the minimum duration of disinfection of 10 3 ml of wastewater it took about 30 s at a discharge energy of 5 J ml −1 . The advantages of bacterial inactivation in wastewater by high-voltage spark discharges were revealed, such as low operating voltage of 10 kV, high energy efficiency of 600 J l −1 and capacity 30 l h −1, increased service life and operational reliability, portability and environmental friendliness. Highlights: The application of wastewater for irrigation in agriculture has been proposed. Effect of spark discharges on the total bacterial count in wastewater was tested. Reduction of total bacterial count in wastewater to norm 10 6 CFU ml −1 was in 120 s. Achieved high energy efficiency 600 J l −1 and capacity 30 l h −1 . Disinfection of wastewater by spark discharges is more environmental friendliness.